Transformative Management Innovation in Islamic Education: Enhancing Institutional Adaptability, Efficiency, and Educational Relevance - Syarip Syarip; M. Sirozi; Mardiah Astuti (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Despite growing scholarly attention to management innovation in Islamic education, existing research remains theoretically fragmented, with limited integration of governance, leadership, curriculum, and technology into unified analytical frameworks. This systematic literature review (SLR) critically synthesizes and theorizes management innovation by identifying dimensions, analyzing interconnections, and proposing an integrated analytical framework. Following PRISMA 2020, we searched Scopus (2015–2025) using TITLE-ABS-KEY Boolean terms: (